The Influence of Job Satisfaction and Work Motivation Toward Employee Performance in PT Indomarco Prismatama Pontianak - Anggraini, Masithah B1024141016 (Jurnal Manajemen Update, 2019)
The purpose of this study was to determine the description of job satisfaction, work motivation and employee performance in PT Indomarco Prismatama Pontianak and analyse how much the influence of job satisfaction and work motivation toward employee performance. The sample in this research was 120 employees from PT Indomarco Prismatama Pontianak.            The measurement of this study is using a Likert scale and analysed using SPSS 22. The tests which have been done are validity, reliability, classic assumption test, R square test and T test in order to analyse the relationship of all variables. Based on the research result, it can be known that job satisfaction and work motivation had positive and significant relationship on employee performance with coefficient of determination as much as 84 percent, while the other 16 percent is influenced by other variables which were not been analyzed in this research.